2021
DOI: 10.1186/s12889-021-11235-4
|View full text |Cite
|
Sign up to set email alerts
|

Work-life balance predicted work ability two years later: a cohort study of employees in the Swedish energy and water sector

Abstract: Background Work-life balance (WLB) is the extent to which individual’s multiple life roles and demands carry over between each role. WLB can be divided into work interference with personal life (WIPL) and personal life interference with work (PLIW). This study aimed to investigate longitudinal associations between WIPL, PLIW and work ability outcomes. Methods In this cohort study, 224 employees in the energy and water sector in Sweden were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
(69 reference statements)
1
6
0
Order By: Relevance
“…Our empirical evidence indicated that work and family are essential life domains, and balance between these two domains is crucial for PWA. In this regard, our findings align with other quantitative studies that have established a relationship between work-family or work-life balance and WA (Abdelrehim et al 2023;Berglund et al 2021). Our research showed that the work and non-work domains are intricately intertwined and cannot be examined separately.…”
Section: Discussionsupporting
confidence: 91%
“…Our empirical evidence indicated that work and family are essential life domains, and balance between these two domains is crucial for PWA. In this regard, our findings align with other quantitative studies that have established a relationship between work-family or work-life balance and WA (Abdelrehim et al 2023;Berglund et al 2021). Our research showed that the work and non-work domains are intricately intertwined and cannot be examined separately.…”
Section: Discussionsupporting
confidence: 91%
“…To assess the components of work-life balance, a 24-item scale developed by Fisher, Bulger and Smith (2009) was adopted for the present study. Similar studies in the recent past also adopted Fisher, Bulger and Smith (2009) work-life balance item scale in other contexts (Matthews, Wayne and Ford, 2014;Irawanto, Novianti, and Roz, 2021;Berglund, et al, 2021). For both scales adopted by the present study, exploratory factor analysis has been conducted to ascertain the construct validity of the scales.…”
Section: Measures Of Occupational Stress and Work-life Balancementioning
confidence: 93%
“…Abdullah et al (2022) studied WLB and JS in Chhattisgarh. In addition to the above Berglund et al (2021) studied the influence of WLB on the predicted work ability of employees in Sweden. Thilagavathy and Geetha (2023) systematically reviewed literature on WLB, Tamunomiebi and Oyibo (2020) systematically reviewed WLB and employee performance and concluded that systemic barriers are hindering implementation of the policies on WLB in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Examination of the extent to which WLB, health and well-being in European welfare states can be a balancing act ( Lunau et al, 2019 ) and the influence of JS and WLB on the job performance of female Nurses, and lastly, the influence of WLB on JS ( Abdullah et al, 2022 ). Other empirical studies on WLB include Agha et al (2017) , Qureshi et al (2019) , Berglund et al (2020) , Ahmad and Raja (2021) , Pehlivanoğlu et al (2022) , Bocean et al (2023) , Cheung G. W. et al (2023) , and Gupta and Agrawal (2023) . Most of the studies used cross-sectional surveys and literature reviews as their designs.…”
Section: Introductionmentioning
confidence: 99%